Inquisitive investigations. - Kee, Ya Ting. (2012)
Science, a “systematic study and knowledge of natural and physical phenomena” (Holmes, 2003, p.513), has always been an integral part of life on Earth. More than the technological advances that have transformed the conditions and quality of life, however, the study of science has also consistently shaped the way we view ourselves within the universe we live in; and it is this very relationship between Man and Science that forms the basic premise for my project. This paper will chronicle and discuss the conceptual development, work process and relevant influences that have been integral towards the completion of my Final Year Project (FYP).